Bacterial Load of Chlamydia trachomatis in the Posterior Oropharynx, Tonsillar Fossae, and Saliva among Men Who Have Sex with Men with Untreated Oropharyngeal Chlamydia - Phillips, Tiffany R. (J Clin Microbiol, 2019)
The aim of this study was to determine whether Chlamydia trachomatis could be detected in saliva and if infection is specific to an anatomical site in the oropharynx. Men who have sex with men (MSM) who were diagnosed with oropharyngeal chlamydia at the Melbourne Sexual Health Centre in 2017-2018 were invited to participate upon returning for treatment. Swabs at the tonsillar fossae and posterior oropharynx and a saliva sample were collected. Throat samples were tested for C. trachomatis by the Aptima Combo 2 assay. The bacterial loads of C. trachomatis in all samples were assessed by quantitative PCR (qPCR) detecting the ompA gene. We calculated the positivity and bacterial load of C. trachomatis for all samples. Forty-two MSM were included. The median age was 28 years (interquartile range [IQR], 24 to 33 years). Thirty-two participants (76.2%; 95% confidence interval [CI], 60.5% to 87.9%) had C. trachomatis detected by qPCR at both the tonsillar fossae and the posterior oropharynx, followed by 9.5% (n = 4; 95% CI, 2.7% to 22.6%) positive at the posterior oropharynx only and 4.8% (n = 2; 95% CI, 0.58% to 16.2%) positive at the tonsillar fossae only. Twenty-nine MSM had C. trachomatis detected in saliva (69.0%; 95% CI, 52.9% to 82.3%). The median C. trachomatis load in saliva was 446 copies/ml (IQR, 204 to 1,390 copies/ml), that in the tonsillar fossae was 893 copies/swab (IQR, 390 to 13,224 copies/ml), and that in the posterior oropharynx was 1,204 copies/swab (IQR, 330 to 16,211). There was no significant difference in C. trachomatis load between the tonsillar fossae and the posterior oropharynx (P = 0.119). Among MSM with oropharyngeal chlamydia, nearly three-quarters had chlamydia DNA detected in saliva, although the viability and implications for transmission are unknown.